ENHANCEMENT COPING STRESS WITH CREATIVE ART - Abidah Ayu (International Conference on Social and Islamic Studies, 2021)
Coping is an individual's ability to respond to stress, which will harm physical and psychological. Coping involves managing a stressful situation, then extending that effort to solve life's problems and trying to cope with and reduce stress. Coping can be done by focusing on problems and emotions. For example, problem coping will focus on solving individual problems first. In contrast, emotional coping will focus on efforts to relieve negative emotions to become more positive in solving problems. Based on research, creative art can be used as therapy for adults and children, including improving coping skills. The types of art therapy that can be applied are drawing, music, dancing, playing, and all other forms of creative art.